Inverse Secant of Imaginary Number

From ProofWiki
Jump to navigation Jump to search

Theorem

$\sec^{-1} x = \pm i \sech^{-1} x$


Proof

\(\displaystyle y\) \(=\) \(\displaystyle \sec^{-1} x\)
\(\displaystyle \implies \ \ \) \(\displaystyle \sec y\) \(=\) \(\displaystyle x\) Definition of Inverse Secant
\(\displaystyle \implies \ \ \) \(\displaystyle \sech \paren {i y}\) \(=\) \(\displaystyle x\) Secant in terms of Hyperbolic Secant
\(\displaystyle \implies \ \ \) \(\displaystyle i y\) \(=\) \(\displaystyle \sech^{-1} x\) Definition of Inverse Hyperbolic Secant
\(\displaystyle \implies \ \ \) \(\displaystyle y\) \(=\) \(\displaystyle -i \sech^{-1} x\) multiplying both sides by $-i$

$\blacksquare$


Sources